Respuesta :

Answer:

[tex]-1\frac{1}{3}[/tex] or [tex]\frac{4}{3}[/tex]

Step-by-step explanation:

This can be represented by the equation [tex]\frac{x+12}{2} =4-x[/tex].  

To solve, we first multiply both sides by 2 to remove the fraction on the left. This leaves us with [tex]x+12=8-2x[/tex]

Next, we subtract 12 from both sides to get [tex]x[/tex] by itself. This results in [tex]x=-2x-4[/tex].

Then we add [tex]2x[/tex] to get the [tex]x[/tex]-term on only one side. We get [tex]3x=-4[/tex].

Dividing by 3 to get [tex]x[/tex] by itself, the equation becomes [tex]x= -\frac{4}{3}[/tex].

ACCESS MORE